Trend Mapping of Traditional Ceremonial Studies: Systematic Literature Review - Syam, Syahrianti; Wandi, Wandi (International Journal of Social Service and Research, 2024)
The rising popularity of traditional rituals and ceremonies globally, including in Indonesia, has sparked interest both as heritage practices passed down through generations and as contemporary subjects of study. This article aims to provide a comprehensive overview of trends in the study of traditional ceremonies through a systematic literature review. However, the current abstract falls short of elucidating the specific criteria used to select the 200 articles. To address this, the study employed a systematic literature review approach, examining 200 scholarly articles on traditional ceremonies sourced from Google Scholar and Crossref databases spanning the years 2012 to 2022. The systematic literature review utilized the Publish or Perish application to gather metadata from Google Scholar and Crossref, with subsequent data visualization facilitated by the VOSviewer application. The outcomes of the study encompass three main findings: 1) Mapping clusters of study themes related to traditional ceremonies, 2) Identifying the network of authors whose works predominantly contribute to the field of traditional ceremonies, and 3) Uncovering gaps and novel aspects within the realm of traditional ceremony studies. While the abstract outlines these results, a more detailed elaboration is essential to enhance the overall depth and contribution of the study. Specifically, elucidating the criteria used for article selection and providing a more thorough explanation of the mapping clusters and identified gaps will significantly improve the clarity and impact of the research.